Age-of-Acquisition effects in word and picture identification. [article]. - Juhasz, B.
Words and pictures with earlier learned labels are processed faster than words and pictures with later learned labels. This age-of-acquisition (AoA) effect has been extensively investigated in many different types of tasks. This article provides a review of these studies including picture naming, word naming, speeded word naming, word pronunciation durations, lexical decisions, eye fixation times, face recognition, and episodic memory tasks. The measurement and validity of AoA ratings is discussed, along with statistical techniques used for exploring AoA's influence. Finally, theories of AoA are outlined, and evidence for and against the various theories is presented. -- (from the author)